The Unity Of Personality Ideas Of Kant, Hegel, Nitshe, Vaintsvaig, Plato, David The Invicible And Garegin I, Benedict Xvi - Aleksandr Bagdoev (Imastut'yun, 2015)
In the present paper theories of creative personality are considered, developed by great philosophers, social psychologists, humanists, and also by representatives of religious confessions. On base of known triad of Hegel about subjective, objective and absolute spirit is done relative gradation of personality, which is containing in each man: ‘Empiric’, ‘Social’ and ‘Super empiric’ man or simply creative subject in all aspects. All this is related also to gradation of whole peoples and states. On this base it is shown complete coincidence of, on first sight contrary theories of personality. It is shown, that often first and second types of man demonstratively break laws of mentioned categories, pursuing in their actions, unnecessary for nobody momentary benefits and ‘victories’. As it was mentioned by Pope Benedict, the rescue of the Mankind is in the rapprochement and in community of all religions in general for all these doctrines, the creation of an image of the pure high strong personality. There aren’t any differences between these doctrines. The analysis of many contemporary problems in psychology and ethics of individuals and nations in terms of priority common to all approaches to relationships of modern conditions of the individual and society, of all countries and peoples are given.